2014
DOI: 10.14348/molcells.2014.2359
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin Is Involved in Peptidylarginine Deiminase 2-Induced Apoptosis of Activated Jurkat Cells

Abstract: Peptidylarginine deiminase type 2 (PADI2) deiminates (or citrullinates) arginine residues in protein to citrulline residues in a Ca2+-dependent manner, and is found in lymphocytes and macrophages. Vimentin is an intermediate filament protein and a well-known substrate of PADI2. Citrullinated vimentin is found in ionomycin-induced macrophage apoptosis. Citrullinated vimentin is the target of anti-Sa antibodies, which are specific to rheumatoid arthritis, and play a critical role in the pathogenesis of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…The citrullination PTM of GFAP and vimentin, reported as due to the action of the Protein-arginine deiminase type-2 (PAD2) enzyme in brain tissue [35,36], produces the loss of charge of the arginine residue, resulting in longer chromatographic retention time (see Figure 1 as an example) of the modified peptide due to its increased hydrophobicity. This PTM alters the folding and the biological function of the protein, and it is reportedly involved in the pathogenesis of autoimmune diseases, inflammation, tumor biology, and progression [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The citrullination PTM of GFAP and vimentin, reported as due to the action of the Protein-arginine deiminase type-2 (PAD2) enzyme in brain tissue [35,36], produces the loss of charge of the arginine residue, resulting in longer chromatographic retention time (see Figure 1 as an example) of the modified peptide due to its increased hydrophobicity. This PTM alters the folding and the biological function of the protein, and it is reportedly involved in the pathogenesis of autoimmune diseases, inflammation, tumor biology, and progression [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Another report described that the levels of antibody against phosphorylcholine were negatively associated with atherosclerosis development in hypertensive individuals, and low levels of this antibody independently predicted the development of cardiovascular disease [35]. Furthermore, vimentin and heat shock proteins had increased expression on the cell surface of apoptotic cells [36,37]. Therefore, naturally occurring autoantibodies against vimentin and heat shock proteins may contribute to the regulation of immune homeostasis in neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We generated a line of Jurkat cells that express an exogenous PAD2 in an inducible manner (43). We found that inducing the expression of PAD2 increased the expression of Th17 cytokines but inhibited the expression of Th2 cytokines ( Figure 6C).…”
Section: Hypercitrullination In Pbmcs Of Healthy Aris the Observatiomentioning
confidence: 96%